The Impact of the Islam and Religious Moderation Course on Students’ Moderate Behaviour: The Mediating Role of Attitude in Islamic Higher Education - Fahrurrozi Fahrurrozi; Mustaqim Mustaqim; Lulut Dwi Ratna; Sirojul Fuad; Mustopa Mustopa (Madania: Jurnal Kajian Keislaman, 2025)
This study examines the impact of religious moderation course services—namely course materials, learning strategies, and learning environment—on students' moderate behaviour, mediated by their attitudes. The research was conducted at UIN Walisongo with a sample of 215 students who had taken the course "Islam and Religious Moderation." The collected data were analyzed using regression analysis, F-test, t-test, and path analysis with the assistance of SPSS version 23. The findings reveal varying relationships among course materials, learning strategies, learning environment, attitudes, and moderate behaviour. Simultaneously, course materials, learning strategies, and learning environment significantly influence students' moderate attitudes. However, only learning strategies do not significantly affect students' moderate attitudes when examined individually. Furthermore, in different patterns, course materials, learning strategies, learning environment, and moderate attitudes collectively influence students' moderate behaviour, yet only learning strategies individually influence moderate behaviour. Additionally, only course materials and learning environment affect moderate behaviour through students' moderate attitudes. These findings underscore the importance of enhancing course services to foster students' moderate attitudes and behaviours, both directly and indirectly. Penelitian ini bertujuan untuk menguji pengaruh layanan perkuliahan moderasi beragama (materi kuliah, strategi pembelajaran, lingkungan belajar) terhadap perilaku moderat yang dimediasi dengan sikap moderat mahasiswa. Penelitian ini dilakukan pada mahasiswa UIN Walisongo dengan jumlah sampel 215 mahasiswa yang telah mengambil mata kuliah “Islam dan Moderasi Beragama.” Data-data yang terkumpulkan selanjutnya dianalisis dengan menggunakan model analisis regresi, f test, t test, dan path analysis yang dibantu dengan program SPSS versi 23. Hasil penelitian menunjukkan hubungan yang bervariasi antara variabel materi kuliah, strategi pembelajaran, lingkungan belajar, sikap, dan perilaku moderat. Secara simultan materi kuliah, strategi pembelajaran, dan lingkungan belajar mempengaruhi sikap moderat mahasisiwa, namun secara parsial hanya strategi pembelajaran yang tidak mempengaruhi sikap moderat mahasiswa. Secara simultan materi belajar, strategi pembelajaran, lingkungan belajar, dan sikap moderat, dalam pola yang berbeda, mempengaruhi perilaku moderat mahaiswa, namun hanya strategi pembelajaran yang mempengaruhi perilaku moderat mahasiswa. Selanjutnya hanya materi belajar dan lingkungan belajar yang mempengaruhi perilaku moderat melalui sikap moderat mahasiswa. Temuan penelitian ini mengaskan perlunya penyempurnaan layanan perkuliahan agar membentuk sikap dan perilaku moderat mahasiswa secara langsung maupun tidak langsung.